The Earning Management Valuation: Effects of Tax Incentives on Hotel Sector in Malaysia - Pritam Singh, Gurcharan Singh (2000)
This study examines the implication of optimizing earning management from tax incentives granted by the government to the hotel sector in Malaysia. Visit Malaysia Year, 1990 saw Pioneer Status and Investment Tax Allowance being introduced to the Hotel Sector, which qualifies as a promoted product or promoted activity in promoting tourism in the country. These changes in earnings are investigated by decomposing earnings and by isolating the tax change component resulting from the actual and expected tax expenses. Earnings and the tax component are regressed with security returns. In line with this, using event methodology, the immediate effect of the announcement is observed for any abnormal gains.Results show that there is significant correlation between the effective tax change and the security returns. In addition there is a short term monetary effect due to the announcement. However the market anticipates the information well before the official announcement with positive abnormal returns prior and on the announcement day.